2014
DOI: 10.4111/kju.2014.55.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Interfraction Prostate Movement in Bone Alignment After Rectal Enema for Radiotherapy

Abstract: PurposeTo assess the effect of a rectal enema on interfraction prostate movement in bone alignment (BA) for prostate radiotherapy (RT), we analyzed the spatial difference in prostates in a bone-matched setup.Materials and MethodsWe performed BA retrospectively with data from prostate cancer patients who underwent image-guided RT (IGRT). The prostate was identified with implanted fiducial markers. The setup for the IGRT was conducted with the matching of three fiducial markers on RT planning computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…There was no prospective randomized study comparing enemas to any other intervention, with most studies making comparisons with either retrospective cohorts 17 or previous published results. [22][23][24] The 1 small prospective study resulted in some improvement with reduced rectal volume and accompanying anterior-posterior prostate motion. 13 However, the rectal volume was only measured along the length of the prostate, which excludes the superior section of the rectum where the maximum changes occur, thus making comparison with other studies (where measurements of average rectal volume have been determined using the whole length of the rectum) difficult.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There was no prospective randomized study comparing enemas to any other intervention, with most studies making comparisons with either retrospective cohorts 17 or previous published results. [22][23][24] The 1 small prospective study resulted in some improvement with reduced rectal volume and accompanying anterior-posterior prostate motion. 13 However, the rectal volume was only measured along the length of the prostate, which excludes the superior section of the rectum where the maximum changes occur, thus making comparison with other studies (where measurements of average rectal volume have been determined using the whole length of the rectum) difficult.…”
Section: Discussionmentioning
confidence: 95%
“…It is interesting that 1 of the studies suggested that care professionals administering the enemas may be a more effective strategy than self-administration. 24 There is also known variability between subjects in the ease of administering bowel preparation regimens and a difficulty in achieving rapid, reproducible, and effective cleansing with minimal discomfort. 25,26 Despite these drawbacks the use of enemas coupled with clear guidance on timing, use, and recording of rectal dimensions warrants further investigation with accompanying data regarding patient compliance, which is currently lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rectal enemas have been effective in reducing intrafraction prostate motion in this study and in another 17 and have also been reported to be efficient in decreasing interfraction prostate movement. 16,18 On this basis, we think that the use of rectal enemas is a feasible method for reducing prostate movement during RT.…”
Section: Discussionmentioning
confidence: 99%
“…Intermodality shifts between the different technologies seem comparable, as reported by Mayyas et al 20 Among the methods, localization using markers results in the least interuser disagreement compared with using anatomy or soft tissues. 14,21 Different authors have reported that the choice of imaging frequency and timing are key components in delivering the desired dose while reducing the associated overhead, such as imaging dose, preparation, and processing time.…”
Section: Image Gated Radiotherapy Strategiesmentioning
confidence: 99%